Total Hyphema with Light Perception Vision Managed by Anterior Chamber Washout: A Case Report - Rofwiun; Nurul Elyana (The International Journal of Medical Science and Health Research, 2026)
Introduction Ocular trauma represents a major etiology of monocular blindness and visual morbidity, frequently requiring emergent ophthalmological evaluation to prevent permanent deficits.1 Traumatic hyphema, defined as the presence of blood within the anterior chamber, typically arises from blunt or penetrating force that disrupts the vascular integrity of the iris or ciliary body.3 While most hyphemas are self-limiting, high-grade presentations (Grade III and IV) pose a significant risk for secondary complications such as ocular hypertension, secondary glaucoma, and corneal blood staining.5 The management of these cases is particularly complex in the immediate postoperative period following intraocular surgery, where the structural stability of the eye is already compromised.8 Case Illustration A 64-year-old male presented with a chief complaint of sudden vision loss, severe ocular pain, and redness in the right eye (OD) after an accidental hand strike during sleep. The patient was one week postoperative following a Small Incision Cataract Surgery (SICS). Initial examination revealed a visual acuity of light perception (LP), an intraocular pressure (IOP) of 21.9 mmHg, and a Grade IV total hyphema with evidence of fibrin clots. Slit-lamp biomicroscopy confirmed corneal edema and a hazy anterior chamber. Despite three days of intensive conservative management using postural therapy, topical steroids, anti-glaucoma agents, and systemic antifibrinolytics, the visual acuity did not improve. Consequently, a surgical anterior chamber washout was performed. Discussion Total hyphema, often referred to as an "eight-ball" hyphema when clotted and deoxygenated, necessitates a careful balance between medical observation and surgical intervention.3 In this case, the recent surgical history and the stagnant nature of the clotted blood increased the risk of permanent endothelial damage and optic neuropathy.6 The choice of an anterior chamber washout as a minimally invasive procedure was pivotal in evacuating the blood and restoring aqueous dynamics.8 Pharmacological support using Indonesian-branded medications such as Bralifex Plus and Hyaloph, combined with comprehensive antioxidant supplements like Asta Plus and Retivit Plus, facilitated the recovery of the ocular surface and neuroprotection.13 Conclusion Anterior chamber washout is an effective and safe intervention for non-resolving total hyphema in the early postoperative phase.8 Prompt surgical evacuation, when medical therapy fails to produce clinical improvement within 72 hours, is essential to prevent irreversible complications and ensure significant visual recovery.6